Représenter l’espace par la carte dans les manuels scolaires en Iran (1973-2012) - Alice Bombardier (EchoGéo)
Through a corpus of eight textbooks of Geography and Persian language, published in Iran before or after the Islamic Revolution and reserved for primary or secondary school, this article analyses the rank of the map from a graphic, semeiological and discursive point of view. Original cartographic scenarios are highlighted. Both the situation of the map in the image system and its role in the “iconicisation” of the national territory and in the representation of the world are presented. This examination of school cartography processes in Iran brings out the contribution of geography to the territory and national identity production in a multi-ethnic and multi-linguistic society.